XIX. YY. SONLARI İLE XX. YY BAŞLARINDA YAKUTSK BÖLGESİ İNSANLARININ GİYİM VE TAKILARI - Yakovleva, Dr. Kapitolina; Yakovlev, Aital (Hayrettin İVGİN, 2014)
19. yy’ın sonları ile 20. Yy’ın başlarındaki Sibirya ve Uzak Doğudaki Rus kasabaları günümüzde önemli bir ilgi çekmektedir. O dönemdeki insanların giysileri ve takıları kültürün en önemli yansıtıcısı olarak geleneksel eski biçimlerin korunması ve yeniliklerin ortaya çıkışı Yakutların görüntülerinde takip edilebilir. The subject of provincial Russian towns of the late XIX – early XX centuries especially Siberian and Far East ones, have become very popular nowadays. Man’s clothing and accessories of that time is the most important part of his culture which reflects the problem of preservation of traditional archaic forms and appearances of novelty, which is also observed in the image of Yakutsk’s residents. Темы провинциального российского города конца XIX – начала XX в., в особенности сибирских и дальневосточных городов, приобрели сегодня особую актуальность. Одежда и украшения человека того времени — важнейшая часть его культуры, в которой отражается проблема сохранения в ней традиционных архаичных форм и появление новообразований, что так же наблюдается во внешнем облике горожан Якутска.